XIX. Tożsamość czytelniczki - Paja, Agnieszka (Instytut Badań Literackich Polskiej Akademii Nauk, 2024)
This book is impressive in its range of research and the wealth and diversity of sources collected. The extent of the area of nineteenth-century literature covered by the inquiry and analysis (justifiably extended to the first decade of the twentieth century), situated in the network of communication connections, allows for the author’s work on the aspect of the then standards of normalising and practising reading among women to be seen as pioneering. The issues covered here are: journalism pieces, published in several dozen magazines and as separate editions, promoting conservative, liberal and socialist views; novels by well-known authors, but also by the marginalised ones; collections of comments by the female readers. Agnieszka Paja pays the same level of attention to the words by men and women, she highlights independent opinions, as well as those shaped by Western figures of authority. The author does not overlook the differences in consciousness of the acclaimed female writers and the ‘mediocre’ female readers, she refers to historical testimony, and discerns the readings of literary heroines. The clarity and composition of the book is undoubtedly worth highlighting and appreciating. (Dr hab. Urszula Kowalczuk)